2011
DOI: 10.1016/j.ijar.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Most probable explanations in Bayesian networks: Complexity and tractability

Abstract: An overview is given of definitions and complexity results of a number of variants of the problem of probabilistic inference of the most probable explanation of a set of hypotheses given observed phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 31 publications
0
64
0
Order By: Relevance
“…The parameterized complexity class FPT consists of all fixed parameter tractable problems κ−Π. While traditionally κ is defined as a mapping from problem instances to natural numbers (e.g., Flum & Grohe, 2006, p. 4), one can easily enhance the theory for rational parameters (Kwisthout, 2011). In the context of this paper, we will in particular consider rational parameters in the range [0, 1], and we will liberally mix integer and rational parameters.…”
Section: Complexity Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…The parameterized complexity class FPT consists of all fixed parameter tractable problems κ−Π. While traditionally κ is defined as a mapping from problem instances to natural numbers (e.g., Flum & Grohe, 2006, p. 4), one can easily enhance the theory for rational parameters (Kwisthout, 2011). In the context of this paper, we will in particular consider rational parameters in the range [0, 1], and we will liberally mix integer and rational parameters.…”
Section: Complexity Theorymentioning
confidence: 99%
“…This result holds for networks with only binary variables, with at most three incoming arcs per variable, and no evidence. In addition, Kwisthout (2011) showed that it is NP-hard in general to find an explanation approxsol B with Pr(approxsol B , e) > for any constant > 0, and thus that Pr(optsol B , e) − Pr(approxsol B , e) ≤ ρ for ρ > Pr(optsol B , e) − . The latter result holds even for networks with only binary variables, at most two incoming arcs per variable, a single evidence variable, and no intermediate variables (i.e., when we approximate an MPE problem).…”
Section: Value-approximationmentioning
confidence: 99%
See 3 more Smart Citations